2016
DOI: 10.1111/ijpp.12273
|View full text |Cite
|
Sign up to set email alerts
|

‘Repeat’ prescriptions and antibiotic resistance: findings from Australian community pharmacy

Abstract: Health system factors may contribute to inappropriate antibiotic use in Australia, including availability and validity of repeat antibiotic prescriptions. Government health departments, prescribers, pharmacists, other health professionals and consumers have to share the responsibility of ensuring that antibiotics are used appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Medicines dispensed in the original fixed packaging may result in under‐ or oversupply of antibiotics leading to either suboptimal duration of treatment or ‘leftover’ antibiotics. A recent WHO survey found that a quarter of patients would share the leftover antibiotics . There is significant probability that these leftover antibiotics, whose use would be uncontrolled, unsupervised and possibly inappropriate, contribute to development of antimicrobial resistance .…”
Section: Discussionmentioning
confidence: 99%
“…Medicines dispensed in the original fixed packaging may result in under‐ or oversupply of antibiotics leading to either suboptimal duration of treatment or ‘leftover’ antibiotics. A recent WHO survey found that a quarter of patients would share the leftover antibiotics . There is significant probability that these leftover antibiotics, whose use would be uncontrolled, unsupervised and possibly inappropriate, contribute to development of antimicrobial resistance .…”
Section: Discussionmentioning
confidence: 99%